Sublethal pesticide exposure influences behaviour, but not condition in a widespread Australian lizard. Issue 1 (24th April 2022) - Contador-Kelsall, Isabella; Maute, Kimberly; Story, Paul; Hose, Grant C; French, Kristine
Abstract : Reptiles are overlooked in ecotoxicological research. We assessed the impacts of two commonly used pesticides, fipronil and fenitrothion, on a widespread Australian lizard, using ecologically relevant exposure. Fipronil reduced activity by ≥49% but did not impact physiological measures. Fenitrothion exposure did not result in detectible changes to behaviour or physiology. Abstract: Assessment of non-target impacts of pesticides used widely in agriculture and pest management rarely considers reptiles. Despite their integral role in all ecosystems, particularly arid ecosystems, reptiles are not included in risk assessments. Two pesticides used in agricultural pest management are fipronil and fenitrothion. Here, we used a field-based BACI design experiment in semi-arid Australia to investigate the impact of these pesticides on basic physiological and behavioural parameters of a common arid-zone lizard species, Pogona vitticeps . Fipronil and fenitrothion were applied at ecologically relevant doses via oral gavage. Before and after dosing, blood, physical activity and body condition parameters were assessed. We found that temperature significantly influenced lizard activity in the morning period of movement; however, fipronil-treated individuals moved at least 49% less than fenitrothion-treated and control lizards from 7 days after dosing through to the end of the experiment. Physiological measures did not change significantly before or after exposure to both pesticides; however, other indicators showed evidence of exposure, which remained for the entirety of our monitoring period. On average, cholinesterase inhibition was still >30% compared with control lizards at the end of 4 weeks, and fipronil sulfone blood residues remained at 0.219 μg/ml. Our study provides novel insights into the impacts that common pesticides have on widespread lizard species. We show that an ecologically relevant low dose of fipronil alters the behaviour of P. vitticeps, which has the potential to impact longer-term survivability. Persistence of both pesticides in the blood of all treatment lizards throughout the experiment indicates they are unable to clear these toxins within a month of being exposed. This may be significant for compounding exposure and latent toxicity. These findings highlight the susceptibility that reptiles have to a selection of common pesticides and the inherent need for higher prominence in wildlife ecotoxicological research.